Finite element analysis of elastomer used in automotive suspension systems. (October 2020) - Karthikeyan, R; Rajkumar, S; Bensingh, R Joseph; Kader, M Abdul; Nayak, Sanjay K
Present research endeavours towards the development of a methodology to enhance the life of hyperelastic materials in automotive suspension (leaf spring) system. The durability of the elastomeric (rubber) material in the insert was determined at various loading conditions for better operation. Three different rubber materials were used as the models including the currently used rubber material in the suspension system. The non-linear finite element analysis was carried out for the three different materials with the uniaxial stress–strain data as the input source for the material properties. A suitable hyperelastic model was also used as the input for determining the deformation and the stress concentration in the leaf spring tip insert. The failure of the tip insert was determined in various loading conditions and the best design for limited stress concentration with higher reliability was determined in the three models. The overall results are tabulated and compared for better utilization of rubber as a tip insert in the automotive industry.